Teaching Strategy in English Speaking Class - Tiarannisa Putri Lestari; Julianthi Zefana Silitonga; Ayonia Jelita Boru Sinaga; Erma Sujiyani; Muhammad Subhan Fikri (Journal of English Language Learning, 2025)
This study aimed to explore the lecturer’s teaching strategies in the speaking class at Universitas Palangka Raya. This study used a qualitative research design. The participant in this study was one of the lecturers who taught in the Intermediate English-Speaking Class during the 2nd semester. The instruments used were a field note and an interview guide. The study found that the lecturer employed various strategies to teach speaking skills, depending on the topic of the day. The lecturer employed seven strategies throughout the class activity. In the opening, the lecturer would use icebreakers as a warm-up. In the core activity, the lecturer would employ techniques such as brainstorming, drilling, pair work, role-playing, and group work. At the end of the class, the lecturer would play a game named “Exit Ticket”. This study is recommended for lecturers or teachers as a reference for teaching speaking skills.